Citizenship Ecological in Citizenship Education: Strengthening Awareness Environment in Secondary Education - Vinna Dinda Kemala; Ryan Taufika; Nadziroh; Vinni Dini Pratiwi; Alil Rinenggo (Academy of Education Journal, 2026)
This study aims to explore the process of integrating ecological citizenship into Civic Education (PKn) learning in secondary schools, as well as identifying its impacts, challenges, and implementation strategies within the context of the Kurikulum Merdeka. Using a qualitative approach with a single-case study design, this study was conducted in a high school in Medan City with Adiwiyata status. Data were collected through multi-source techniques including in-depth semi-structured interviews with Civic Education teachers and the principal, non-interventional participant observation during six class sessions, critical analysis of curriculum documents, and three student Focus Group Discussions (FGDs). All qualitative data were analyzed interactively using the Miles, Huberman, and Saldaña model with open and axial coding techniques. The results showed that the integration of ecological citizenship through active-participatory strategies, the "Sustainable Lifestyle" project, and the Green Living Values ​​(GLV) syntax significantly increased ecological empathy (moral feeling) and encouraged students' real actions (moral action), while reconfiguring their thinking paradigm from anthropocentrism to ecocentrism. However, the effectiveness of this implementation is still limited by structural challenges, including a civics curriculum heavily weighted toward formal state administration, teachers' limited ecopedagogical capacity, and limited green facilities in schools. This study concludes that strengthening ecological citizenship requires reform of national curriculum policies, ongoing ecopedagogy and postdigital literacy training for teachers, the implementation of a whole-institution approach, and multi-stakeholder collaborative synergy between schools and local communities.